Pengembangan Media Pembelajaran Audio Visual Untuk Meningkatkan Hasil Belajar Pada Mata Pelajaran IPAS - Marhaini, Marhaini; Ali, Muhamad; Nursaly, Baiq Rismarini (Educatio, 2025)
Technological advances in education demand innovation in learning media to support the quality of the teaching and learning process. This study aims to develop and test the effectiveness of audio-visual learning media in IPAS subjects, especially on ecosystems and biodiversity. The method used is Research and Development (R&D) with the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 15 fourth grade students of SDN 1 and 2 Sembalun Lawang, with the results of a 3-minute 30-second video showing an increase in student understanding. From the results of the analysis, 10 students achieved a “High” N-Gain classification (≥ 0.7), with two students achieving the highest scores of 0.962 and 0.926, indicating that this audio-visual media is effective in improving understanding of the material. The learning media developed has been validated by experts and received positive responses from students and school principals, who assessed this media as feasible and effective in increasing student motivation and learning outcomes. This research shows that audio-visual media plays an important role in overcoming the challenges of IPAS learning and has a significant positive impact on student motivation and understanding, making it reliable as a technology-based learning approach